China’s long march to gas price freedom: price reform in the people’s republic - O'Sullivan, S (Oxford Institute for Energy Studies, 2018)
China is the world’s third-largest gas market – as well as its fastest-growing. Government policy, economic growth and reform of its gas pricing system are driving growth in demand at double-digit rates. The outlook for China’s gas market and its interaction with the wider world of global gas is both a major question for international gas players as well as for Chinese policymakers. While it is primarily government policy driving gas demand today, through the coal-to-gas switching programme underway in northern China, once that ends gas pricing will be the key driver of demand. The government faces a challenge of choosing between low domestic prices to stimulate demand and improve the environment or high prices to encourage domestic production and restrain the country’s rising dependence on expensive imports – particularly in a challenging international political environment. The current pricing structure is a hybrid of regulation and market linkages – albeit moving in the right direction. We identify and analyse the success stories of price reform in China and the challenges that government and industry still face – not all of them pricing-related, since they include midstream reform, infrastructure construction and access, the development of gas hubs and the inevitably serious challenge from renewables.